ECT in an Adolescent With Schizophrenia and Seizures: Case Report - Gralewicz, Anna; Świȩcicki, Łukasz; Antosik-Wójcińska, Anna Z.; Konopko, Magdalena; Kurkowska-Jastrzȩbska, Iwona; Sienkiewicz-Jarosz, Halina; Szostakiewicz, Łukasz; Remberk, Barbara (Frontiers in Psychiatry, 2021)
Electroconvulsive Therapy (ECT) has been recognized as an effective treatment option in catatonia, for prolonged or severe affective episodes and schizophrenia. Response rates vary from 40 to 80% in adolescents. The procedure is safe, if the required precautions are undertaken. Nonetheless, ECT remains a serious clinical challenge in patients with comorbid seizures. We present a case study of a 17-year-old female student suffering from schizophrenia who was scheduled for ECT due to prior treatment inefficacy. Seizures had occurred a few days before the first ECT session. Nevertheless, the patient received the ECT course, combined with clozapine at 125 mg/d, after neurological diagnosis and treatment modification because the illness became life-threatening. The patient’s clinical outcome was satisfactory without any seriously adverse events and further improvements were observed in the mental state following long-term psychosocial treatment at our inpatient unit. A few months later epilepsy was however diagnosed with probably coexistence of partial seizures and seizure-like events of non-epileptic etiology. Administering ECT in patients with seizure comorbidity was also investigated based on previous research. To the best of our knowledge, the safety and efficacy of using ECT in adolescents with schizophrenia and seizures has not yet been discussed in the literature.